Kollektivierung als Herausforderung für das Strafrecht Normentheoretische Betrachtungen - Papathanasiou, Katharina; Schumann, Kay H.; Schneider, Anne; Fernandes Godinho, Inês (Grundlagen des Strafrechts, 2021)
This conference volume presents a multifaceted criminal law analysis of the concept of collectivisation, especially from the perspective of norm theory. First of all, the participation theory is taken up: Kindhäuser highlights problems of the collective commission of an offence by going to the semantic level of the discussion. Schneider looks at the international-criminal-law reference to participation. Bock deals with the concrete regulation in § 184j StGB. Subsequently, questions of attribution are addressed: Renzikowski discusses the possibility of considering collectives as subjects of imputation on the basis of legal philosophy. Wagner deals with the debate on the responsibility of principals. The volume is rounded off by two further aspects: Godinho highlights the relationship between collectivity and norm formation. Rösinger deals with the collectivisation of dangers and thus with aggressive necessity.